Development of a payload for monitoring biological samples in microgravity and hypergravity conditions - Canto-Vivanco, Elber E.; Ramos-Cosi, Sebastian; Romero-Alva, Victor N.; Vargas-Cuentas, Natalia I.; Roman-Gonzalez, Avid (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
This research aims to address the need for monitoring the behavior of organic and inorganic materials in hypergravity conditions. To fulfill this objective, a container with specific features was designed. The container has a box with a lid, measuring 10×10×10 cm, conforming to the 1U volume of the CubeSat standard. It includes four cylindrical spaces to accommodate the sample wells. The container was 3D printed using polylactic acid (PLA) wire. For the electronic components, four ESP32-CAM modules were utilized, with two programmed to capture and upload photos to the cloud, and the other two programmed to capture and store photos on a micro SD memory card. Additionally, four light emitting diodes (LEDs) were incorporated to illuminate the well spaces. The total weight of the container is 450 grams, and it has a maximum wireless upload distance of 10 meters to the cloud. The storage capacity of the SD memory card determines the number of images that can be saved.